MODEL OF MOTIVATION TO SUCCESS AMONG EMPLOYEES OF PRODUCTION TEAMS: CONTENT AND ANALYSIS OF COMPONENTS - Alina V. Yudina (Вісник Університету імені Альфреда Нобеля. Серія Педагогіка і психология)
The article describes the theoretical generalization and practical application of model motivation to success of employees from production collectives. The article presented the author’s model of motivation to success among employees from production collectives. We considered motivation to success in this model as an interaction of employees’ motivational types with entrepreneurial skills, communicative and organizational inclinations, team roles, position, and gender. We analyzed the motivation to success in the context of production companies’ work activity and in employees’ behavior in production collectives. To our mind, the motivation of employees is a combination of external and internal driving forces, which stimulate person’s activity and set forms of this activity to achieve the goal. The theoretical study considers the essence and content of employees’ work motivation. We created the author’s model of motivation to success in employees of production collectives. This model claims the motivation to success to be an interaction of motivational types in employees with their entrepreneurial skills, communication and organizational inclinations, team roles, position, and gender. Our empirical study reveals the peculiarities of motivation to success in employees of a chemical production enterprise. We developed some types of employees’ motivation: achieving to success – high motivation to success and low motivation to avoidance, motivated – high motivation to success and high motivation to avoidance, avoiding failures – low motivation to success and high motivation to avoidance, unmotivated – low motivation to success and low motivation to avoidance. The article studies differences in motivational types among employees. The motivational types of employees in production collectives have been related to communicative and organizational inclinations. The employees of production collectives, who refer to the motivational type for achieving success have higher level of communicative and organizational inclinations. The entrepreneurial skills in the context of studying psychological features of motivation to success in employees of production collectives were examined. The entrepreneurial skills of employees are: the needs for achievement, creativity inclination, commitment and determination, the ability to take reasonable risk, the need for independence. The employees’ communicative and organizational inclinations were also studied. We also presented types of motivation among employees from production collectives, which were developed by the author on the basis of an empirical study of motivation to success and motivation to avoidance of failure. We distinguished the following motivational types: achieving success, avoiding the failures, motivated, unmotivated. The article shows the results of the study of specificity in the relationship between motivational types and entrepreneurial skills, communicative, organizational inclinations, and team roles among employees from production collectives. We implemented the analysis of the results of studying relationship between the components of model motivation to success of employees from production collectives with motivational types. The research showed a significant correlation of employees’ position and gender with motivational types. High motivation to avoidance of failures affects the manifestation of team roles among employees from production collectives in different ways. ISSN 2522-4115 (print) ВІСНИК УНІВЕРСИТЕТУ ІМЕНІ АЛЬ